Developing Student Book Based on Ethnomathematics to Improve Student’s Critical Thinking Skill - Irma Risdiyanti; Dwi Sulisworo (IKIP Siliwangi, 2021)
The current world conditions have led to the life of the 21st century with all the very rapid changes in civilization and the challenges that future generations must face. So it is necessary to prepare students to have creative skills to adapt and face challenges in the 21st-century era. In the implementation of the 21st curriculum in Indonesia, it needs to be adapted to Indonesia's existing context. In alternative mathematics learning, an approach that can be used is Indonesian Realistic Mathematics Education ( PMRI) with the context of Ethnomathematics. This study aims to develop ethnomathematics-based multimedia to support the development of PMRI-based learning using the ethnomathematics context. The method used in this research is design research with the type of development studies. The data collection technique was done by interviewing, distributing questionnaires, and studying literature. The data were then analyzed using a qualitative descriptive analysis. The results of this study are a student book product and the results of the analysis of student responses to these products. This research is expected to become a foundation in developing mathematics learning designs using ethnomathematics contexts to improve student critical abilities.